A FOSTERING TOLERANCE THROUGH RELIGIOUS MODERATION: STRATEGIES IN ISLAMIC EDUCATION - Mukhsin (IHTIROM : Jurnal Manajemen Pendidikan Islam, 2024)
Abstract: The development of the globalization era, marked by social diversity and the spread of foreign ideologies, has made religious moderation an urgent necessity in the education system. This study aims to identify the strategies employed by teachers at SMA Negeri 1 Kencong to instill values of tolerance and moderation in students, particularly in a context with diverse religious, cultural, and social backgrounds. The research uses a qualitative approach with a case study design, involving teachers and students in Islamic Religious Education. Data collection techniques include in-depth interviews, participatory observation, and document analysis. Data were analyzed using the Miles and Huberman (1994) method, which includes data reduction, data presentation, and conclusion drawing. The results show that instilling values of tolerance and moderation through innovative methods such as group discussions and simulations successfully enhances students' empathy toward differences. The integration of materials in the PPKn and Indonesian language curricula, along with parental and community involvement, also contributes to the improvement of tolerance attitudes. Academic recommendations from this study include the development of specialized learning modules focusing on values of tolerance and moderation to further strengthen students' character in a diverse society.